2020
DOI: 10.1002/ajoc.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐free Nucleophilic Alkoxylation of in Situ‐Generated Azaoxyallyl Cations: Synthesis of Hindered Dialkyl Ether Derivatives

Abstract: A metal and catalyst-free, environmentally friendly synthesis of hindered dialkyl ether derivatives has been established via the nucleophilic alkoxylation of alcohols and α-halohydroxamates. The reactions of a variety of primary and secondary alcohols with azaoxyallyl cations generated in situ from α-halohydroxamates afforded a wide range of hindered dialkyl ether derivatives in good yields. Moreover, methods for the synthesis of α-alkoxyhydroxamic acids, α-alkoxy amides, and α-hydroxy amides from αalkoxy hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…and Kim et al. pioneeringly established aza‐oxyallyl cation as alkylating agent [8c–f] . In 2020, Singh and co‐workers synthesized pharmaceutically important congested secondary aryl amines by treating aniline derivatives with aza‐oxyallyl cations (reactive form of functionalized alkylating agent α ${\alpha }$ ‐halo amides) under basic condition in HFIP solvent [8c] .…”
Section: Aza‐oxyallyl Cations As An Alkylating Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…and Kim et al. pioneeringly established aza‐oxyallyl cation as alkylating agent [8c–f] . In 2020, Singh and co‐workers synthesized pharmaceutically important congested secondary aryl amines by treating aniline derivatives with aza‐oxyallyl cations (reactive form of functionalized alkylating agent α ${\alpha }$ ‐halo amides) under basic condition in HFIP solvent [8c] .…”
Section: Aza‐oxyallyl Cations As An Alkylating Agentmentioning
confidence: 99%
“…Inspired by the above achievements Kim et al., in the same year reported C−O alkylation with aza‐oxyallyl cation. They synthesized wide range of hindered dialkyl ether derivatives 126 through metal and catalyst free, base mediated nucleophilic alkoxylation of primary and secondary alcohols 125 with aza‐oxyallyl cation in aprotic fluorinated solvent CF 3 C 6 H 5 with good yields [8e] . Screening results showed that Cs 2 CO 3 in CF 3 C 6 H 5 was the optimal reaction condition for the said transformation (Scheme 38).…”
Section: Aza‐oxyallyl Cations As An Alkylating Agentmentioning
confidence: 99%
See 1 more Smart Citation